Are the Best and Brightest Joining the Public Service?. (September 2020) - Fowler, Luke; Birdsall, Chris
The changing nature of public service has blurred the lines between economic sectors by intermingling public, private, and nonprofit missions, and made it easier for employees to balance extrinsic and intrinsic motivators by seeking employers positioned along a continuum that balance their interests. Using data from the "After the JD" study, the authors analyze responses of law school graduates to determine how academic qualifications and employee motives affect economic sector of employment. Findings suggest that the best and brightest law school graduates are predisposed to employment in the private or nonprofit sectors because they offer the strongest extrinsic or intrinsic incentives.